Development strategies and regional income disparities in China - Justin Yifu Lin; Peilin Liu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper argues that the regional income gap of China is endogenously determined by its long-term economic development strategy. Development strategies can be broadly divided into two mutually exclusive groups: (i) the comparative advantage-defying (CAD) strategy, which attempts to encourage firms to deviate from the economy's existing comparative advantages in their entry into an industry or choice of technology; and (ii) the comparative advantage-following (CAF) strategy, which attempts to facilitate the firms' entry into an industry or choice of technology according to the economy's existing comparative advantages. Since the founding of the People's Republic of China, the government has pushed a CAD strategy, i.e., `leap forward' strategy that emphasized the development of capitalintensive heavy industries. In most provinces, however, the priority industries under this strategy were inconsistent with the comparative advantage determined by the factor endowments in those provinces. Many enterprises in the priority industries were not viable in competitive markets and required interventions in the markets by the government to support and protect them. Consequently, the CAD strategy retarded the functions of market, impeded capital accumulation and hindered technology and productivity progress in the provinces. After the reform, the provinces in the central and western regions continue to follow the CAD strategy and have poor growth performance. Therefore, it is imperative to replace the CAD strategy with a CAF strategy and restructure the existing industries in each province according to the principle of comparative advantage. This latter strategy would lead to balanced development among regions and provinces.
Keywords: O18; O53; P20; P25; 330; economic development strategy; regional income disparities; viability; China; economy; Regionale Einkommensverteilung; Entwicklungsstrategie; China